Bowling for communism : urban ingenuity at the end of East Germany - Demshuk, Andrew, 1980- (Cornell University Press, 2020)
"This book shows how civic life functioned in East Germany's second-largest city on the eve of the 1989 Revolution by uncovering illegal and semi-legal acts of 'urban ingenuity' amid catastrophic urban decay"--